Hubungan Pengetahuan dengan Peran Masyarakat dalam Pencegahan Seks Bebas (Pranikah) pada Remaja di Rw 02 Dukuh Kleco Desa Sawoo - Santi Kanthi Suci Handayani; Dwi Setyorini; Laviana Nita Ludyanti (STIKES Karya Husada Kediri, 2018)
Adolescence is a unique transitional period due to physical, psychological and social changes. Physicalchanges occur faster than psychological and social changes. Sexual hormones have begined to workencouraging teenagers to perform various types of sexual behavior. Prevention of free sex (before gettingmarried) in adolescents can be prevented by the positive role of community by used the role of educators, rolemodels, companions, counselors, communicators, and friend. This study aims to analyze the relationship ofknowledge with the role of community in the prevention of free sex (before getting married) in adolescents.Correlational research design with all of people in RW 02 Kleco Sawoo Village with the aged 26-65 years, withpurposive sampling technique 54 respondents. Research result most of the respondents (42,4%) had enoughknowledge, as many 23 respondents. While most respondents (44,4%) had enough role, as many as 24respondents and there is a relationship of knowledge with the role of the community in free sex prevention(before getting married) in adolescent p value = 0,000 < 0,05, the relationship levels are strong and positive(correlaton coefficient 0,669), this means that the better the community knowledge the role of community is alsobetter, the researcher suggest to the next researcher to researched and directly observed the role of communityin the prevention of free sex (before getting married).